Ancient philosophy within a global purview: Parmenides and Zhuangzi on expressing what can (and cannot) be known - Cantor, L (2023)
This Thesis argues that widespread misconceptions about the early history of philosophy hamper engagement with ancient philosophy within a global purview. I identify and challenge an influential narrative according to which philosophy emerges through a shift from mythos to logos (Chapter 1). This framework misrepresents the history of ancient Greek philosophy and simultaneously underpins the perceived illegitimacy of ‘non-Western’ traditions as philosophical traditions. I examine how this same narrative creates major interpretive blind spots within specialist work on ancient philosophy (Chapters 2–5). I do so by exploring two consequential cases, two foundational philosophers in early Greek and classical Chinese philosophy, respectively: Parmenides and Zhuangzi.